The Concept of Community Housing Construction System Planning in Responding to Natural Conditions in Coastal Settlements - Imriyanti .; Nasruddin .; Pratiwi Mushar; Hartawan .; A. Lolo Sinrang A; Annisa Putri Bachtiar; Alia Salsabila Farhani; Marzon Maisi; Muh. Nurhalim A (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The location of settlements in coastal areas that does not pay attention to rules and limits in residing often experiences natural disasters such as tidal floods, abrasion, and strong winds, causing losses to the residents. Beba Hamlet, Tamasaju Village, Galesong Utara District, Takalar Regency has settlements in coastal areas. Natural disasters have become an important issue in considering the resilience of the community's housing construction system that is able to respond to natural conditions in coastal environments. The goal is to find a concept for addressing the problems of communities living in coastal areas so that their homes can withstand natural disasters. Before implementation, the public response to the concept was as follows: 47.4% (in the enough category) of the community did not understand the concept; 57.4% felt the concept did not meet the community's needs; 63.7% thought the concept was not useful; 52.1% believed the concept did not provide a level of safety against natural disasters. After the concept's implementation, the results were: 85.9% of the community were able to understand the concept; 60.5% felt the concept met the community's needs in handling natural disasters; 83.7% of the community thought the concept was very useful; 81.1% believed the concept could provide safety through the reconstruction and renovation of homes in Beba hamlet, Tamasaju village.